Rubus fruticosus L.: constituents, biological activities and health related uses - Zia-Ul-Haq, Muhammad; Riaz, Muhammad; De Feo, Vincenzo; Jaafar, Hawa Z.E.; Moga, Marius (MDPI, 2014)
Rubus fruticosus L. is a shrub famous for its fruit called blackberry fruit or more commonly blackberry. The fruit has medicinal, cosmetic and nutritive value. It is a concentrated source of valuable nutrients, as well as bioactive constituents of therapeutic interest highlighting its importance as a functional food. Besides use as a fresh fruit, it is also used as ingredient in cooked dishes, salads and bakery products like jams, snacks, desserts, and fruit preserves. R. fruticosus contains vitamins, steroids and lipids in seed oil and minerals, flavonoids, glycosides, terpenes, acids and tannins in aerial parts that possess diverse pharmacological activities such as antioxidant, anti-carcinogenic, anti-inflammatory, antimicrobial anti-diabetic, anti-diarrheal, and antiviral. Various agrogeoclimatological factors like cultivar, environmental conditions of the area, agronomic practices employed, harvest time, post-harvest storage and processing techniques all influence the nutritional composition of blackberry fruit. This review focuses on the nutrients and chemical constituents as well as medicinal properties of different parts of R. fruticosus. Various cultivars and their physicochemical characteristics, polyphenolic content and ascorbic acid content are also discussed. The information in the present work will serve as baseline data and may lead to new biomedical applications of R. fruticosus as functional food.